Wendy Mann, FAO, on Climate-Smart Agriculture at UNFCCC SB40 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
FAO's Senior Policy Advisor on agriculture and climate change, Wendy Mann, explains about the FAO EPIC programme's Climate-Smart Agriculture-projects, the links between CSA and adaption and mitigation and also the role of agriculture in the UNFCCC process.